c.2 - Chopra, Sanjeev (ed.) (Dehradun, 1999)
This book is more than a compilation of papers, articles and group discussions at the first regional consultation on the subject: it is an effort to search newer horizons for co-operative enterprises and place the issues of co-op policy, vis-a-vis recent trends in legislation and the experiences of disengagement of government.
Keywords: Cooperatives